Zapalenia spojówek – alergia czy zespół suchego oka? - Bogacka, Ewa; Groblewska, Anna (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2009)
Red eye is a common condition of contemporary people. We have to remember that allergy is not the only cause of red eye. Most frequently, conjunctivitis is infective in origin, but both allergic and infective conjunctivitis may coexist with dry eye syndrome. To investigate and solve this problem, collaboration of the ophthalmologist and allergologist is often necessary. This article is a guide proposition first of all for general practitioners, but also for other specialists. It consists of two steps: the questions which should be asked to the patient, and basic examination of the eye. In this way most mild allergic conjunctivitis can be diagnosed and treated successfully. The differential diagnosis of “red eye” and the urgent causes of this sign are also presented in this article.